Drawing as Driver of Creativity: Nurturing an Intelligence of Seeing in Art Students. (12th October 2017) - Riley, Howard
Abstract: The article reasserts the primacy of drawing as a driver of creativity within art schools. It reviews specific aspects of visual perception theory and visual communication theory relevant to a pedagogical strategy as a means of nurturing an 'intelligence of seeing' in art students. The domain of drawing is theorised as a systemic‐functional semiotic model informed by Michael Halliday's model for language, as adapted by Michael O'Toole in his 2011 The Language of Displayed Art . The model is demonstrated as an aid to the production of drawings, rather than its more‐recognised efficacy as a means of negotiating meaning from existing works. The article is illustrated with examples of drawings by the author.